Usaha Tani Padi (Oryza sativa L.) dalam Perspektif Kelembagaan Adat: Peran Komunitas Buluttana di Kabupaten Gowa, Sulawesi Selatan - M. Zain, Majdah; Fitrianti, Fitrianti; Ibrahim, Helda; Yunus, Awaluddin (Universitas Batangahari Jambi, 2025)
This study aims to explore more deeply how the structure and role of Buluttana customary institutions can adapt to existing social, economic, and policy changes, and find solutions that can strengthen the sustainability of their agricultural management amidst globalization and modernization. The type of research is qualitative descriptive, with a historical approach. The source of research data is primary data, namely data sourced from the results of observations, interviews and documentation from customary leaders, community leaders, and the community in Buluttana, Secondary data is data that the author obtained through reading and literature, as well as other information related to this research and using purposive sampling techniques. Data collection methods were obtained using interview methods, observation, documentation, literature studies, and the use of questionnaires. Respondents in this study were 60 farmers. The results of the study showed several substantive things, namely that the determination of planting time in Buluttana traditional farming begins with holding a deliberation, land processing is carried out by mutual cooperation using agricultural tools in the form of hoes and small tractors (dragonfly tractors), seed selection is carried out through a selection process involving traditional elders or senior farmers, Buluttana traditional communities rely more on natural fertilizers sourced from the surrounding environment, such as manure, straw ash, rotten leaves and compost that are processed traditionally, irrigation water management is not only technical, but also social and spiritual through the existence of traditional figures called pinati, determination of harvest time is based on observations of the ripeness of rice grains, which is usually carried out by experienced farmers or traditional figures and the majority of the rice harvest is stored for personal consumption where only a small portion is sold to the local market or through informal channels such as barter or sold to neighbors and relatives. The conclusion of this study is that the rice farming pattern in the Buluttana traditional community shows the full involvement of all respondents in every stage of agricultural activities as a whole..